The day the earth said enough! - Litre, Gabriela; Curi, Melissa; Bursztyn, Marcel; Drummond, José Augusto (Sustainability in Debate, 2016)
Each year our Planet reaches its biocapacity earlier. In 2016, we reached this threshold in the beginning of August. This means that one again humanity used all natural resources available for the entire year, in less than eight months. Sadly, August 8th was the Planetary Overshoot Day. It marks the moment when our demand on nature overcomes its ability to regenerate itself during the year. Starting August 8th, 2016, we are therefore in debt with the natural environment. We do not pay any interest rates…, but our children will certainly feel the consequences.